Development of dielectric barrier discharging power supply. (October 2015) - Gao, Yinghui; Liu, Kun; Fu, Rongyao; Sun, Yaohong; Yan, Ping
Abstract: Due to the demand of a dielectric barrier discharge power supply, a high voltage and high frequency AC power supply was designed and implemented. Its output voltage is standard or approximate standard sine waveform with the frequency range of 1 kHz to 50 kHz. The output voltage and output frequency can be adjusted individually. The maximum output power of the power supply is 2 kW. It can be operated through local or remote control. The power supply has been used in the dielectric barrier discharging research under different conditions.